A 'Kees' Study on Nominal Record Linkage - Gerrit Bloothooft (Historical Life Course Studies)
This paper describes a case study on nominal record linkage on data from the Mandemakers family. It is demonstrated how names from birth, marriage and death certificates can be used for fast, probabilistic, ego-based record linkage, with the help of year of birth to arrive at unique identification. The procedure includes name standardization to overcome variation in spelling and the use of probabilities of combinations of given names and surnames, computed from the digitized 19th century Dutch vital register.